Infiltration distribution rates on areas affected by rapid erosive process and covered by anthropogenic materials - Mathias, Dener Toledo (2018)
In this paper, infiltration distribution rates were evaluated on areas affected by accelerated erosive processes and covered by anthropogenic material. Infiltration tests were performed at several samples distributed in the area. The data were adjusted to the Horton decay function, and its parameters were correlated with attributes of the physical environment and the terrain digital model, using the Pearson correlation coefficient (r). Results pointed out great variability of infiltration rates, due to the complexities generated by several structural interventions in the different sectors sampled, with different morphological, granulometric and land use variables. The analysis made sector by sector here proposed allowed verifying the main variables that interfere in the parameters that represent the infiltration rates, in spite of the spatial variability for infiltration rates. In low-slope sectors, there was a strong correlation between infiltration rates and sand, as well as between these rates and river distance. In high slope and grassland areas, such correlations are high between the final infiltration rates and the fine materials (clay and clay + silt). In high-slope areas with no vegetation coverage, the strongest correlations occur between the final infiltration and the cumulative runoff flow. Therefore, results here presented emphasize that both the characteristics of the cover materials and the morphology of the land are determinant for data analysis.